«Արարատ»-ը՝ Մայր Աթոռ Սուրբ Էջմիածնի տարեգիր - Սերժ Սրապիոնյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается почти полувековая деятельность журнала «Арарат», представляются идея и цели его основания, а также направленная на благо народа деятельность Первопрестольного Святого Эчмиадзина.Рассказывается о проектах архиепископа Гавриила Айвазовского, Газароса Агаяна и других редакторов, в частности, о нововведениях Католикоса Всех Армян Мкртича Первого Ванеци. The article considers nearly 50-year old activity of “Ararat” magazine. The idea and aims of its creation, as well as the patriotic activity of the Mother See of Holy Etchmiadzin are also described. It presents the projects of the editor-in-chief Archbishop Gabriel Ayvazovsky, Ghazaros Aghayan and others, and in particular the innovations of Mkrtich I of Van, Catholicos of All Armenians.
Keywords: Periodicals; Christianity; History of the Armenian Church